2016
DOI: 10.1080/10494820.2016.1189943
|View full text |Cite
|
Sign up to set email alerts
|

Traditional vs. innovative uses of computers among mathematics pre-service teachers in Serbia

Abstract: This study examined pre-service teachers' intentions to use computers in traditional and innovative teaching practices in primary mathematics classrooms. It extended the technology acceptance model (TAM) by adding as external variables pre-service teachers' experience with computers and their technological pedagogical content knowledge (TPCK). Data collected from 226 participants revealed that the proposed model had a good fit for both traditional and innovative uses of computers. Structural equation modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 51 publications
1
23
0
2
Order By: Relevance
“…Moreover, Liu (2011) identified a positive effect of TPACK on attitudes (β = .31) and found support for direct as well as indirect effects on the usage intentions. Focusing on traditional and innovative forms of ICT use, Teo, Milutinović, Zhou, and Banković (2016) and Avidov-Ungar and Eshet-Alkalai 2011confirmed the positive and significant relations between overall TPACK, perceived usefulness, and general ICT attitudes. An element common to these studies is that both TPACK and attitudes were represented by overall scores as indicators, without specifying their specific facets.…”
Section: Tpack-attitudes Relationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, Liu (2011) identified a positive effect of TPACK on attitudes (β = .31) and found support for direct as well as indirect effects on the usage intentions. Focusing on traditional and innovative forms of ICT use, Teo, Milutinović, Zhou, and Banković (2016) and Avidov-Ungar and Eshet-Alkalai 2011confirmed the positive and significant relations between overall TPACK, perceived usefulness, and general ICT attitudes. An element common to these studies is that both TPACK and attitudes were represented by overall scores as indicators, without specifying their specific facets.…”
Section: Tpack-attitudes Relationsmentioning
confidence: 86%
“…In fact, negative perceptions of the usefulness of technology and its ease might create barriers for their integration into teaching and learning Teo et al, 2008). In this regard, we encourage researchers to study the interactions between attitudes and TPACK in the context of technology acceptance (Hsu, Liang, Chai, & Tsai, 2013;Teo et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies on e-learning acceptance have indicated attitude as a determinant factor of behavioural intention toward e-learning usage (e.g., Cheung & Vogel, 2013 ; Tosuntaş et al, 2015 ). Attitude is found to be a dominant factor to influence behavioural intention (Chu & Chen, 2016 ; Hussein, 2017 ; Teo, 2012 ; Teo et al, 2017 ; Zogheib et al, 2015 ). Drawing upon the findings of those studies, we formulated the following hypothesis.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The previous studies using experience as an external factor of TAM model looked at different types of users of e-learning, namely, employees (Lee et al, 2011 , 2013 ; Purnomo & Lee, 2013 ), students (Lau & Woods, 2008 ; Rezaei et al, 2008 ; Williams & Williams, 2010 ), students and educators (Martin, 2012 ), and teachers (De Smet et al, 2012 ). Furthermore, prior studies used various kinds of experiences, such as internet experience (Premchaiswadi et al, 2012 ), technology experience (Al-alak & Alnawas, 2011 ; Teo et al, 2017 ), computer efficacy as user’s prior experience (Waheed & Jam, 2010 ), and online learning experience (Liu et al, 2010 ). However, a few studies used e-learning experience in high school as an external factor to examine university students’ behavioural intention toward e-learning utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the work at hand selects behavioral intention as the outcome variable. Perceived ease of use and perceived usefulness are principal variables of individuals’ technology acceptance ( Hao et al, 2017 ; Teo et al, 2017 ). Job relevance as one of the external factors was described as a firm association with perceived usefulness ( Pituch and Lee, 2006 ).…”
Section: Literature Reviewmentioning
confidence: 99%